2015
DOI: 10.1007/s00280-015-2833-5
|View full text |Cite
|
Sign up to set email alerts
|

Albumin-bound nanoparticle (nab) paclitaxel exhibits enhanced paclitaxel tissue distribution and tumor penetration

Abstract: Purposenab-paclitaxel demonstrates improved clinical efficacy compared with conventional Cremophor EL (CrEL)-paclitaxel in multiple tumor types. This study explored the distinctions in drug distribution between nab-paclitaxel and CrEL-paclitaxel and the underlying mechanisms.MethodsUptake and transcytosis of paclitaxel were analyzed by vascular permeability assay across human endothelial cell monolayers. The tissue penetration of paclitaxel within tumors was evaluated by local injections into tumor xenografts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 38 publications
5
65
0
Order By: Relevance
“…Albumin has a high affinity for hydrophobic drugs including PTX [4] and is transported across the endothelial barrier of blood vessels through binding to the gp60 albumin receptor and activation of caveolae-mediated endothelial transcytosis [5][6][7]. Simulations based on population pharmacokinetic modeling showed that the tissue distribution of nab-PTX was more dependent upon an active transport mechanism, i.e., endothelial transcytosis for drug distribution into tissues than that of sb-PTX [8]. A preclinical study in rabbits, in which nab-PTX and sb-PTX were intraperitoneally administered, showed that nab-PTX penetrated the peritoneum tissue better than sb-PTX [9].…”
Section: Discussionmentioning
confidence: 99%
“…Albumin has a high affinity for hydrophobic drugs including PTX [4] and is transported across the endothelial barrier of blood vessels through binding to the gp60 albumin receptor and activation of caveolae-mediated endothelial transcytosis [5][6][7]. Simulations based on population pharmacokinetic modeling showed that the tissue distribution of nab-PTX was more dependent upon an active transport mechanism, i.e., endothelial transcytosis for drug distribution into tissues than that of sb-PTX [8]. A preclinical study in rabbits, in which nab-PTX and sb-PTX were intraperitoneally administered, showed that nab-PTX penetrated the peritoneum tissue better than sb-PTX [9].…”
Section: Discussionmentioning
confidence: 99%
“…This is best reflected by changes in CAF density, which appears to differ in untreated patients and those treated with conventional GS. The nab-paclitaxel also increases the amount of gemcitabine inside tumor cells by inhibiting cytidine deaminase, the enzyme that degrades gemcitabine (24). Because gemcitabine efficacy is reportedly unaltered in myofibroblast and type I collagen-depleted tumors (25), nab-paclitaxel is capable of altering the stroma in PDAC.…”
Section: α-Smooth Muscle Actin (αSma) Expression According To Treatmementioning
confidence: 99%
“…administration while t 1/2 remained the same (Gustafson et al, 2005). This corresponds to studies demonstrating more efficient transport of NPTX across endothelial cells compared to sb-PTX, in which albumin results in an advantageous pharmacokinetic profile (Yardley, 2013;Chen et al, 2015). Figure 6.…”
Section: Discussionmentioning
confidence: 99%